Da hermenêutica musical: relações entre conteúdo e forma do belo musical a partir da leitura gadameriana do juízo estético - Oestreich, Danton Guilherme (Universidade do Vale do Rio dos Sinos, 2016)
Gadamer develops its ontology of the artwork using the play concept to express the mode of being of the work of art, stressing the importance of freeing the concept from the subjective meaning that, since Kant's aesthetics, prevailed in the approach the beautiful art. Judging by the hermeneutic nature of his research, he seems to have in mind the intention of counteracting the need for a art content's historical mediation on the aesthetic notion that favors simple formal distinction of art. In fact, this suggests a confrontation with Kant's notion of free play of the faculties of imagination and understanding, referred to the ideal state of mind when it is inclined to recognize something as beautiful and autonomous from content issues in a perspective of formal distinction. Moreover, for Kant, in the case of works of art, the possibility of beauty judgment would be mediated by the concept of art form in question, where the music ends up being defined as the "beautiful play of ear sensations”. In this way, it should be noted that in music we find a confluence of aesthetic, hermeneutics and formal's dimensions through the same play concept, what allowing the consideration of Gadamer's reading of aesthetic judgment under the peculiarities of musical art. Thus, the purpose of this study is to ascertain the tension between a consideration of the musical beautiful as dependent on an aesthetic autonomy or as endowed with content issues for which the musical form has to be related. This problem situation is presented from the musical form of a specific example – namely: the end of the Hans Werner Henze's Royal Winter Music first sonata – to show how aspects of the theories of Kant and Gadamer can be significant for understanding the musical experience.
Keywords: Belo musical; Hermenêutica filosófica; Juízo estético; Hans-Georg Gadamer; Immanuel Kant; Musically beautiful; Philosophical hermeneutics; Aesthetic judgment; ACCNPQ::Ciências Humanas::Filosofia